Impact of concomitant atrial fibrillation on the prognosis of Takotsubo cardiomyopathy - El-Battrawy, Ibrahim; Lang, Siegfried; Ansari, Uzair; Behnes, Michael; Hillenbrand, Dennis; Schramm, Katja; Fastner, Christian; Zhou, Xiao-Bo; Bill, Verena; Hoffmann, Ursula; Papavassiliu, Theano; Elmas, Elif; et al. (Europace, 2017)
Aims: Previous studies revealed that patients with Takotsubo cardiomyopathy (TTC) have a higher mortality rate than the general population. Supraventricular tachycardia is a well-known complication of TTC. This study was performed to determine the short- and long-term prognostic impact of atrial fibrillation associated with TTC patients. Methods and results: Our institutional database constituted a collective of 114 patients diagnosed with TTC from 2003 to 2015. The patients were divided into two groups according to the presence (n = 21, 18.4%) or absence (n = 93, 81.5%) of atrial fibrillation. The endpoint was a composite of in-hospital events (thromboembolic events and life-threatening arrhythmias), all-cause mortality, rehospitalization due to heart failure, stroke, and the recurrence of TTC. The in-hospital mortality, 30-day mortality, and long-term mortality were significantly higher in the atrial fibrillation group. Kaplan-Meier analysis indicated a significantly lower event-free survival rate over a mean follow-up of 3 years in the atrial fibrillation group than that in the non-atrial fibrillation group (log-rank, P < 0.01). In a multivariate cox regression analysis, atrial fibrillation (hazard ratio, HR 2.3, 95% confidence interval, CI: 1.1-4.9, P < 0.05) and EF ≤ 35% (HR 2.0, 95% CI: 1.1-3.8, P < 0.05) were the only independent predictors of a primary endpoint. Conclusion: Rates of in-hospital events and short- as well as long-term mortality were significantly higher in TTC patients suffering from atrial fibrillation compared with patients without atrial fibrillation.